Estimation of Subfatin, Fetuin-A and other Parameters in Obese Menopause Women (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Menopause is an aging in women, it begins in most of them  at 45 years old, the main reason of menopause is the decline of the Estrogen result from decline of ovaries function, it’s include many of symptoms such as nocturnal sweats, hot flashes, depression, elevated of anxiety, insomnia, sleep disturbance, genitalia include inflammation, dryness, urinary tract infections, painful urination, gaining weight, usually in the abdomen, hips and joint pain. Menopause leads to many disease include insulin resistance, atherosclerosis, chronic hearts disease, obesity, osteoporosis. The adipose tissue it's secretes active proteins such as subfatin which is adipocytokines regulates food intake. Fetuin-A is adipokines and hepatokiens that generated mainly by liver it serves to act as carrier of free fatty acid in circulation. Materials& Methods: Ninety women ages (50-65) participated in the study. (45) non-obese menopausal women with BMI (22.08±3.39) Kg/m2 as a control group. (45) obese women in the menopause with a BMI (35.38±2.52) Kg/m2 as the second group.  أعلى النموذجResults: The results showed that there was a significant decrease at (P≤ 0.01) in the level of Subfatin  and increase at (P≤ 0.01)  in Fetuin-A in the second group compared to the control group. Conclusion: This study found significant negative correlation between Subfatin and lipid profile and significant positive correlation between Fetuin-A and lipid profile.